Recombinant growth hormone for children with systemic lupus erythematosus and linear growth delay: A report of two cases and literature review - Fujuan Liu; Xiaoying Yuan; Yanjun Yang; Yanan Han; Lanlan Ge; Jingxiao Guo; Ling Liu; Chunzhen Li; Dongfeng Zhang (Journal of International Medical Research, 2025)
Linear growth delay is common in children with systemic lupus erythematosus. There have been scattered reports of using recombinant human growth hormone in these children, but safety remains a major concern. We herein report two cases of successful treatment with recombinant human growth hormone in children with systemic lupus erythematosus: a 15-year 10-month-old boy (case 1; disease duration: 4 years; height: 149 cm (<3rd percentile, Z-score <−3); and bone age: 11 years) and a 12-year 8-month-old boy (case 2; disease duration: 5 years; height: 149.5 cm (10th percentile, Z-score = −1); and bone age: 12 years). Both children had been in complete remission for 6 and 30 months, respectively. Insulin-like growth factor-1, insulin-like growth factor-binding protein 3, adrenocorticotropic hormone, and cortisol levels were normal in both cases. Recombinant human growth hormone treatment lasted for 17 and 16 months, respectively. The height increase was 22 and 19 cm during the treatment period, respectively. Systemic lupus erythematosus remained in complete remission on maintenance therapy with hydroxychloroquine/tacrolimus and hydroxychloroquine/mycophenolate mofetil, respectively. Literature search identified two cases. At the time of recombinant human growth hormone treatment initiation, case 1 had proteinuria and elevated serum creatinine level, and case 2 had positive anti-double-stranded DNA antibodies. Relapse occurred immediately after recombinant human growth hormone treatment in both cases. In conclusion, recombinant human growth hormone treatment may be considered for linear growth delay in children with systemic lupus erythematosus if disease activity is sufficiently controlled.